Crowdsourcing Natural History Archives: Tools for Extracting Transcriptions and Data - Mika, Katherine A.; De Veer, Joseph; Rinaldo, Constance (Biodiversity Informatics, 2017)
This paper is a survey of the landscape of current, successful, and innovative platforms for extracting full text transcriptions and structured data using crowdsourcing as a tool. Archival manuscript items are the key case studies reviewed to develop a set of tools for the Biodiversity Heritage Library for use in enhancing access to and extraction information from items in scientific and natural history collections.